Optofluidic sorting of microparticles using Airy beams - Zhelin Qu; Kunpeng Wang; Chao Feng; Tianli Wu; Yao Zhang; Xian Zhao; Jun-Lei Wang (International Journal of Optomechatronics)
Microparticle sorting is a crucial technique with diverse applications spanning biomedical research, microfluidics, and beyond. Conventional methods often face limitations in throughput, precision, and sample integrity. Here we present an optofluidic approach for size-based directional sorting of microparticles using optical manipulation with Airy beams. By harnessing the non-diffracting properties and transverse gradient force of Airy beams, we achieve a non-invasive, high-precision sorting method capable of sorting and selectively clearing microparticles based on their sizes. We also demonstrate more complex operations involving wavefront modulation and microfluidic devices. The proposed method offers effective and versatile microparticle sorting, providing a powerful optofluidic tool for applications requiring precise and efficient sorting of microparticles while maintaining sample integrity.